The reality of Palestinian-European trade relations - Abu Jameh, Akram Fares Mohammed (Arab Journal for Sciences and Research Publishing, 2015)
This study aims at unveiling the reality of Palestinian-European trade relations and at identifying the mechanisms and programs pursued by the European Union to support Palestinian territories. This research studies the impact on economic sectors, productive activities and the access to European trade support for Palestinians by identifying the behavior and the nature of relations between the two sides and the extent of its development. The study revealed the reality of the Palestinian European Economic Partnership and the most important items that express the priority given to Palestine. The research manipulates the descriptive analysis approach, it shows the size and nature of changes in the foreign Palestinian trade with the European Union during the period from 1994 until 2014. It makes use of the latest studies, ideas, previous literature analysis, reports and statistics issued in this area to enrich the study. The study revealed some significant findings: the period in which commercial exchange rate is at best came in line with the availability of an appropriate atmosphere and political optimism. Despite the improved performance of the European support, the Israeli siege and enormous losses of the Palestinian economy might explain the noticeable deceleration in the economic growth rates of the last years. The results unveiled also that the agreements, lines of donations, mechanisms of cooperation, the European Neighborhood agreement. are still below the required level due to the Israeli arbitrary measures, particularly with regard to restricted commercial activity. And this is not consistent with the hypothesis that the Palestinian-European partnership agreement is the only influential item in Palestinian-European economic relations.